2013
DOI: 10.1002/sia.5211
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of laser‐irradiated films of polyvinyl alcohol/starch blends: effect of glycerol content

Abstract: The present paper reports the results of studies on the effect of laser irradiation on the morphology and thermal properties of starch/polyvinyl alcohol (PVA) blend, with varying glycerol concentration. Differential scanning calorimeter results showed that laser irradiation increased the heat of fusion (ΔHfus), heat of crystallization (ΔHcry), temperature of melting (Tm), temperature of crystallization (Tcry) and percentage crystallinity as a function of the amount of glycerol. It is believed that breakdown of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Water-soluble polymers such as PEG and PVA and their blends have found many applications such as packaging [1], cosmetics [2], and emulsifiers and adhesives [3], among others. PVA and its composites have been extensively studied by our group [1,[4][5][6][7][8][9][10][11][12][13][14][15]. With some modifications of the existing polymers, products with low cost and light weight may be developed for a wide range of applications with desirable properties such as mechanical, thermal, and optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Water-soluble polymers such as PEG and PVA and their blends have found many applications such as packaging [1], cosmetics [2], and emulsifiers and adhesives [3], among others. PVA and its composites have been extensively studied by our group [1,[4][5][6][7][8][9][10][11][12][13][14][15]. With some modifications of the existing polymers, products with low cost and light weight may be developed for a wide range of applications with desirable properties such as mechanical, thermal, and optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Previously our group conducted several studies to improve the properties of PVA/starch blends. [ 21–32 ] Sreekumar et al [ 22,23 ] studied the compatibility and effect of plasticizer on the mechanical, thermal and ageing characteristics of starch/PVA blend, keeping the blend ratio as constant. Followed by that, studies conducted by Jose et al [ 27–29 ] showed that the carbon nanotubes and graphene affects the compatibilization there by the physical, mechanical, thermal and dielectric characterization of PVA/starch blend.…”
Section: Introductionmentioning
confidence: 99%